Antiviral activity of bovine type III interferon against bovine viral diarrhea virus is greatly reduced in bovine turbinate cells due to limited expression of IFN lambda receptor 1 (IL-28Rα) - Dassanayake, Rohana P.; Menghwar, Harish; Bickel, Kathryn A.; Holthausen, David J.; Ma, Hao; Diaz-San Segunda, Fayna; Rodriguez-Calzada, Monica; Medina, Gisselle N.; Attreed, Sarah; Falkenberg, Shollie M.; Kanipe, Carly; Sacco, Randy E.; et al. (Frontiers in Immunology, 2024)
Introduction: The antiviral activity of recombinant bovine interferon lambda 3 against bovine viral diarrhea virus (BVDV) has been demonstrated in vitro in Madin-Darby bovine kidney cells (MDBK) and in vivo in cattle. However, anti-BVDV activity of bovIFN-λ3 has not been studied in bovine respiratory tract epithelial cells, supposedly a primary target of BVDV infection when entering the host by the oronasal route. Methods: Here we investigated the anti-BVDV activity of bovIFN-λ3 in bovine turbinatederived primary epithelial cells (BTu) using BVDV infection and immunoperoxidase staining, TCID50, RT-qPCR, DNA and transcriptome sequencing, and transfection with plasmids containing the two subunits, IL-28Rα and IL-10Rβ that constitute the bovIFN-λ3 receptor. Results: Our immunoperoxidase staining, RT-qPCR, and TCID50 results show that while BVDV was successfully cleared in MDBK cells treated with bovIFN-λ3 and bovIFN-α, only the latter, bovIFN-α, cleared BVDV in BTu cells. Preincubation of MDBK cells with bovIFN-λ3 before BVDV infection was needed to induce optimal antiviral state. Both cell types displayed intact type I and III IFN signaling pathways and expressed similar levels of IL-10Rβ subunit of the type III IFN receptor. Sequencing of PCR amplicon of the IL-28Rα subunit revealed intact transmembrane domain and lack of single nucleotide polymorphisms (SNPs) in BTu cells. However, RT-qPCR and transcriptomic analyses showed a lower expression of IL-28Rα transcripts in BTu cells as compared to MDBK cells. Interestingly, transfection of BTu cells with a plasmid encoding IL-28Rα subunit, but not IL-10Rβ subunit, established the bovIFN-λ3 sensitivity showing similar anti-BVDV activity to the response in MDBK cells. Conclusion: Our results demonstrate that the sensitivity of cells to bovIFN-λ3 depends not only on the quality but also of the quantity of the IL-28Rα subunit of the heterodimeric receptor. A reduction in IL-28Rα transcript expression was detected in BTu as compared to MDBK cells, despite the absence of spliced variants or SNPs. The establishment of bovIFN-λ3 induced anti-BVDV activity in BTu cells transfected with an IL-28Rα plasmid suggests that the level of expression of this receptor subunit is crucial for the specific antiviral activity of type III IFN in these cells.